2017
DOI: 10.3324/haematol.2016.156356
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival after acute graft- versus -host disease diagnosis in the modern era

Abstract: A cute graft-versus-host disease remains a major threat to a successful outcome after allogeneic hematopoietic cell transplantation. While improvements in treatment and supportive care have occurred, it is unknown whether these advances have resulted in improved outcome specifically among those diagnosed with acute graft-versus-host disease. We examined outcome following diagnosis of grade II-IV acute graft-versus-host disease according to time period, and explored effects according to original graft-versus-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 14 publications
5
58
1
5
Order By: Relevance
“…The proportion of patients who did not develop aGVHD among the total group of 1215 patients remained steady across the study period, and their survival improved significantly, by 66%, consistent with improvement in supportive care measures for transplant recipients. In contrast to our findings, Khoury et al [30] examined outcomes following a diagnosis of grade II-IV aGVHD by time period and explored effects according to original prophylactic regimen and grade. There was a decrease in the proportion of grade III-IV aGVHD over time (from 56% for 1999 to 2001 to 47% for 2002 to 2005 and 37% for 2006 to 2012), which is reflective of the longer time period analyzed compared with our study which is a more contemporary analysis.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The proportion of patients who did not develop aGVHD among the total group of 1215 patients remained steady across the study period, and their survival improved significantly, by 66%, consistent with improvement in supportive care measures for transplant recipients. In contrast to our findings, Khoury et al [30] examined outcomes following a diagnosis of grade II-IV aGVHD by time period and explored effects according to original prophylactic regimen and grade. There was a decrease in the proportion of grade III-IV aGVHD over time (from 56% for 1999 to 2001 to 47% for 2002 to 2005 and 37% for 2006 to 2012), which is reflective of the longer time period analyzed compared with our study which is a more contemporary analysis.…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, among allo-HCT recipients with a hematologic malignancy who were discharged alive from the hospital, the survival rate was 72.7% in those who developed GI aGVHD, compared with 80.4% in those who did not develop aGVHD. This finding is consistent with a recent study using data from the Center for International Blood and Marrow Transplant Research that found a 40% to 70% 1-year survival rate in patients (N = 1446) who developed grade II-IV aGVHD treated between 2006 and 2012 [30].…”
Section: Discussionsupporting
confidence: 92%
“…Corticosteroids are the mainstay of treatment for acute GVHD, and the prognosis of steroid-refractory disease is poor [69,73]. Prophylaxis against GVHD is an essential part of allogeneic transplant regimens and includes a variety of modalities, including calcinuerin inhibitors, anti-metabolites, and post-transplant cyclophosphamide [74].…”
Section: Acute Graft-versus-host Diseasementioning
confidence: 99%
“…Prophylaxis against GVHD is an essential part of allogeneic transplant regimens and includes a variety of modalities, including calcinuerin inhibitors, anti-metabolites, and post-transplant cyclophosphamide [74]. As GVHD prophylaxis has improved, more patients are presenting with Grade II or Grade III acute GVHD (and fewer are presenting with Grade IV acute GVHD), the incidence of hepatic acute GVHD is decreasing, and overall mortality from acute GVHD is decreasing in patients treated with tacrolimusbased GVHD prophylaxis [73].…”
Section: Acute Graft-versus-host Diseasementioning
confidence: 99%
“…5 In a large registry analysis (n=2905) from the Center for International Blood and Marrow Transplant Research (CIBMTR), they evaluate the incidence and outcomes of grade II-IV acute GvHD developing within 100 days after myeloablative, HLA-matched HSCT over three successive time periods . These periods overlap with important advances in supportive care (e.g., azoles for fungal infections, valacyclovir for cytomegalovirus).…”
mentioning
confidence: 99%